A view into clinical practice guidelines: who uses them, who doesn’t and possibly, why - Mihaela C. Munteanu; Julie Choi Jordan (Qualitative Research in Medicine & Healthcare, 2017)
Medical professional societies each develop specific clinical practice guidelines (CPGs). Based on the best available evidence, CPGs are intended to control variability and optimize quality of care in clinical practice. Yet, healthcare providers often do not accept or adhere to guidelines, but their reasons are not fully understood. When providers opt to choose not to follow CPGs, unfavorable patient outcomes including unequal access to treatment become negative consequences. In this small qualitative study, we will explore what causes non-adherence to CPGs and what changes have been made to CPGs from when physicians completed their medical residencies to the present. We interviewed physicians from a variety of medical specialties to assess how these changes may influence guideline adherence as well as the consequences of not following them. We found that guidelines may not be followed in cases where patients have comorbidities that are not described in the guidelines or when physicians do not incorporate new evidence and technology advances into their practice. In some specialties, physicians can develop a poor reputation if they do not adhere to the CPGs, and managed care agencies may deny reimbursement for care they provided. To best serve the physician and the patient, we need to find ways to improve CPG adherence. Tactics such as improving the methodology of CPG formation, using information technology, and creating ways to change physician attitudes and behavior are all viable options.